Islamic Perspectives on Girl Child Education: A Lesson to Nigerian Hausa Communities - Adam Muhammad Ardo; Adamu Abubakar Muhammad; Yakubu Zulaihat Muhammed (CV Media Inti Teknologi, 2024)
The purpose of this essay is to examine the Islamic viewpoint on female child education in Hausa communities in Nigeria and to talk about the significance of female education from a religious perspective. Additionally, it will look at how Nigerian Hausa communities approach the matter, emphasizing the obstacles girls face in their pursuit of an education as well as the attitudes and beliefs that shape educational procedures. Data was gathered via in-depth reviews of the pertinent literature and conversations with religious leaders, academics, and Hausa community members in order to examine Islamic viewpoints on the education of girls. The study's conclusions showed that Islam views education as a basic human right for all people. It also emphasized the importance of Hausa mothers in educating their daughters and the need for a deeper comprehension of the role that religion plays in promoting girls' educational success. The findings offers the Hausa communities a number of recommendations, such as raising female literacy and educational attainment in Nigerian Hausa communities and promoting the role of mothers in the education of their daughters. Policymakers and practitioners may find the current research helpful in raising awareness of the value of education for girls in Nigeria and around the world.